DESAIN INTERKONEKSI BIOREAKTOR SAMPAH PADAT PERKOTAAN DENGAN MODEL SIRKULASI AIR LINDI ANAEROB UNTUK MENINGKATKAN PRODUKSI GAS METHANE - Septiropa, Zamzami (Jurnal Gamma, 2012)
Desain Interkoneksi Bioreaktor Sampah Padat Perkotaan Dengan Model Sirkulasi Air Lindi Anaerob Untuk Meningkatkan Produksi Gas MethaneZamzami SeptiropaStaf Pengajar Jurusan Teknik Sipil , Fakultas TeknikUniversitas Muhammadiyah Malang,e-mail :  zamseptiropa@umm.ac.idABSTRACTThe existence of gravity of the pressing weight of its own garbage heap of garbage will be squeezed to make trash (pressing) and out of the leachate (Leachate). Contained in the waste leachate has elements glokosa (C6H12O6), Amino Acid and Ammonia (NH3), which will help the growth of anaerobic  bacteria  that  produce  methane  (CH4)  and  carbon  diaoksida  (CO2).  Humidity  will  be reduced as the discharge of garbage in garbage leachate resulting decline in productivity of anaerobic bacteria, thus maintaining levels of humidity (moisture content) is very important in stabilizing the productivity of anaerobic bacteria.In  the  humidity  of  59.85%  productivity  waste  anaerobic  bacteria  produce  landfill  gas  in stagnant in the  range  of  less  than  10%  CH4.  With  a  circulation  process  of  garbage  leachate  to maintain moisture of 67.25% are able to stabilize the production  of landfill  gases, especially CH4 concentration more than 25%. Leachate circulation periodically able to stabilize the moisture content of waste, from which the waste water content, it makes the productivity of stable anaerobic bacteria produce methane gas in concentrations between 20% -25% is quite a power plant of energy.Renewable energy was from waste to be more realistic to be implemented in full scale in place of final processing (TPA) / Landfill.  So the need for energy for the benefit of the power plant could help meet the electricity needs of the community.Keywords: bioreactor anaerobic, leachate circulation